Amyloid fibril formation by bovine cytochrome c. Issue 4 (2005) - de Groot de Groot, Natalia S. Natalia S.; Ventura Ventura, Salvador Salvador
Abstract : Bovine heart cytochrome c is an all- α globular protein containing a covalently bound heme group. Prolonged incubation at 75°C in mild alkaline solution damages the prosthetic group and results in permanent unfolding of the polypeptide chain. Under this conditions, cytochrome c aggregates into fibrillar structures. Characterization by transmission electron microscopy and thioflavin-T binding assays shows that these species posses the characteristics of fibrils associated with the family of amyloid diseases. Our findings indicate that destabilization of the native fold of this highly α -helical protein can lead to its polymerization into β -sheet rich structures and suggest that this process does not depend on the population of partially folded monomeric states with extensive β -sheet structure.